Hubungan Penerapan Family Centered Care Dengan Kecemasan Anak Usia Toddler Di Rumah Sakit Nasanapura - Fennyzar Wulandari; Yuhana Damantalm; Ni Nyoman Udiani (Universitas Widya Nusantara, 2024)
Family center care is an approach that can minimize the occurrence of trauma toward children and families themselves. The pre-survey was conducted on January 28, 2022, in Nasanapura Hospital, among 10 children who observed about 8 children who have anxiety such as crying loudly when they saw the nurses entering their room, crying when we were going to check vital signs, they refuse the therapy so it needs to be persuaded them by their parents. The purpose of the research was to analyze the correlation between the family-centered care performed and the anxiety of toddler-age in Nasanapura Hospital. This type of research is quantitative with an analytical approach using a cross-sectional design. The population in the research were children who were admitted to the Nasanapura Hospital at the time the research was conducted. The total sample was 43 people taken by purposive sampling technique. The results of the research among 43 respondents have good family-centered care for 23 respondents (53.5%) and poor family-centered care for 20 respondents (46.5%). Respondents who are not anxious are about 24 respondents (55.8%) and those who are anxious are about 19 respondents (44.2%). Based on the results of the chi-square test, the p-value is 0.000 (p-value 0.05). The conclusion mentioned that have a correlation between the family-centered care performed with the anxiety of toddler-age in Nasanapura Hospital. Suggestions for hospitals to establish policies for family-centered care performed and nurses as members of the health team who often have contact with patients could provide information and health education to parents about child care.